Targeted metabolomics combined with network pharmacology to reveal the protective role of luteolin in pulmonary arterial hypertension. Issue 20 (29th September 2022) - Song, Kexin; Duan, Qingya; Ren, Jiping; Yi, Jie; Yu, Hong; Che, Haixia; Yang, Chunjuan; Wang, Xiaotong; Li, Qian
Abstract : Luteolin protects from PAH by affecting metabolites and regulatory enzymes' gene and protein levels in the arachidonic acid pathway. Abstract : Pulmonary arterial hypertension (PAH) is a progressive disease that significantly endangers human health, where metabolism may drive pathogenesis: a shift from mitochondrial oxidation to glycolysis occurs in diseased pulmonary vessels and the right ventricle. An increase in pulmonary vascular resistance in patients with heart failure with a preserved ejection fraction portends a poor prognosis. Luteolin exists in numerous foods and is marketed as a dietary supplement assisting in many disease treatments. However, little is known about the protective effect of luteolin on metabolism disorders in diseased pulmonary vessels. In this study, we found that luteolin apparently reversed the pulmonary vascular remodeling of PAH rats by inhibiting the abnormal proliferation of pulmonary artery smooth muscle cells (PASMCs). Moreover, network pharmacology and metabolomics results revealed that the arachidonic acid pathway, amino acid pathway and TCA cycle were dysregulated in PAH. A total of 14 differential metabolites were significantly changed during the PAH, including DHA, PGE2, PGD2, LTB4, 12-HETE, 15-HETE, PGF2α, and 8-iso-PGF2α metabolites in the arachidonic acid pathway, and l -asparagine, oxaloacetate, N -acetyl-l -ornithine, butane diacid, ornithine, glutamic acid metabolites in amino acid and TCA pathways. However, treatment with luteolin recovered the LTB4, PGE2, PGD2, 12-HETE, 15-HETE, PGF2α and 8-iso-PGF2α levels close to normal. Meanwhile, we showed that luteolin also downregulated the gene and protein levels of COX 1, 5-LOX, 12-LOX, and 15-LOX in the arachidonic acid pathway. Collectively, this work highlighted the metabolic mechanism of luteolin-protected PAH and showed that luteolin would hold great potential in PAH prevention.